2018
DOI: 10.1002/rmb2.12254
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous progesterone levels could predict reproductive outcome in frozen embryo replacement cycles supplemented with synthetic progestogens: A retrospective cohort study

Abstract: PurposeA retrospective, cohort study was conducted between 2009 and 2017 in a private infertility center to determine the predictive value of endogenous estrogen (E2) and progesterone (P4) levels in hormone‐replacement frozen embryo replacement (FER) treatment cycles.MethodsA total of 120 consecutive, infertile patients who became pregnant after FER cycles were analyzed (age: 37.4 ± 4.4 years). Electively vitrified blastocysts were created during natural cycle IVF or mild ovarian stimulation treatments and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…We contacted the authors of thirty-two manuscripts to obtain additional study details and data (Supplemental Table 2). To date, we have received responses for ten publications (15,(26)(27)(28)(39)(40)(41)(42)(43)(44).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We contacted the authors of thirty-two manuscripts to obtain additional study details and data (Supplemental Table 2). To date, we have received responses for ten publications (15,(26)(27)(28)(39)(40)(41)(42)(43)(44).…”
Section: Search Resultsmentioning
confidence: 99%
“…Twenty studies have been published as full articles (15, 17, 26-28, 31, 32, 40-45, 47-53) and one as a conference abstract (46). Five of the included studies were conducted in Spain (26-28, 50, 52); three in Japan (32,44,47); two each in Australia (15,51), Denmark (17,45), France (40,41) and Turkey (42,43); and one each in China (53), India (46), Iran (49), Iraq (48) and the USA (31). Eighteen studies focused solely on HRT-FET cycles; two included HRT-FET and fresh donor recipient cycles (26,28); and one study included only NC-FET cycles (52).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A preliminary study conducted in oocyte donation recipients under artificial cycles for endometrial preparation suggested that the onset of placental steroidogenesis surrounded the 5th gestational week ( 19 ), while a more recent study found that endogenous placental activity started on 5 th -6 th pregnancy week, differing significantly according to the pregnancy outcome ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous production of P during pregnancy might occur around week 6, when the uteroplacental shift occurs ( 7 ). Thus, levels of serum P in the mid-late luteal phase transition in artificial cycles could depend exclusively on the exogenous drug that is given to the patient.…”
Section: Introductionmentioning
confidence: 99%